Global environmental commons : analytical and political challenges in building governance mechanisms - Brousseau, Eric. (Oxford : Oxford University Press, 2012)
This text provides an overview of global environmental governance and the effectiveness of different governance mechanisms. Bringing together a broad range of perspectives, it addresses key challenges in contemporary global governance of environmental change.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Environmental economics; Environmental policy